Double aortic arch: a rare cause of wheezing and respiratory distress in infants: a case report - Chakraborty, Abhishek; R., Sanketh; James, Ebor Jacob G. (International Journal of Contemporary Pediatrics, 2022)
Double aortic arch is a rare congenital disorder. Symptoms arises due to compression of trachea or esophagus. Its presentation varies from asymptomatic cases to life threatening respiratory distress. Clinical diagnosis is often difficult due to presence of wide verities of symptoms. We described a three-month-old child presented with wheezing and severe respiratory distress and found to have double aortic arch.